Cell and organ bioengineering technology as applied to gastrointestinal diseases. Issue 5 (20th January 2012) - Orlando, Giuseppe; Bendala, Juan Domínguez; Shupe, Thomas; Bergman, Christopher; Bitar, Khalil N; Booth, Christopher; Carbone, Marco; Koch, Kenneth L; Lerut, Jan P; Neuberger, James M; Petersen, Bryon; Ricordi, Camillo; et al.
Abstract : This review illustrates promising regenerative medicine technologies that are being developed for the treatment of gastrointestinal diseases. The main strategies under validation to bioengineer or regenerate liver, pancreas, or parts of the digestive tract are twofold: engineering of progenitor cells and seeding of cells on supporting scaffold material. In the first case, stem cells are initially expanded under standard tissue culture conditions. Thereafter, these cells may either be delivered directly to the tissue or organ of interest, or they may be loaded onto a synthetic or natural three-dimensional scaffold that is capable of enhancing cell viability and function. The new construct harbouring the cells usually undergoes a maturation phase within a bioreactor. Within the bioreactor, cells are conditioned to adopt a phenotype similar to that displayed in the native organ. The specific nature of the scaffold within the bioreactor is critical for the development of this high-function phenotype. Efforts to bioengineer or regenerate gastrointestinal tract, liver and pancreas have yielded promising results and have demonstrated the immense potential of regenerative medicine. However, a myriad of technical hurdles must be overcome before transplantable, engineered organs become a reality.